2008
DOI: 10.1002/bjs.6324
|View full text |Cite
|
Sign up to set email alerts
|

Fast-track recovery programme after pancreatico- duodenectomy reduces delayed gastric emptying

Abstract: A fast-track programme after PD improves gastric emptying and reduces postoperative stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
198
3
40

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(254 citation statements)
references
References 30 publications
13
198
3
40
Order By: Relevance
“…A meta-analysis of 5 RCTs (176 patients) World Data specifically addressing PONV after PD specifically have not been identified. One comparative (non-randomised) study [7] showed that an ERAS protocol with early mobilisation, metoclopramide and removal of nasogastric tube on day 1 or day 2 decreased the rate of postoperative nausea and vomiting. Until further documentation becomes available, the suggestions for patients undergoing colorectal surgery [3] [122].…”
Section: Summary and Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of 5 RCTs (176 patients) World Data specifically addressing PONV after PD specifically have not been identified. One comparative (non-randomised) study [7] showed that an ERAS protocol with early mobilisation, metoclopramide and removal of nasogastric tube on day 1 or day 2 decreased the rate of postoperative nausea and vomiting. Until further documentation becomes available, the suggestions for patients undergoing colorectal surgery [3] [122].…”
Section: Summary and Recommendationmentioning
confidence: 99%
“…Suprapubic catheterisation is superior to transurethral catheterisation if used for DGE is a specific problem after PD occurring in &10-25 % of patients [6,7,9,170]. It may be necessary to insert a nasojejunal feeding tube in a minority of patients.…”
Section: Summary and Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Berberat et al 8 , Balzano et al 23 and di Sebastiano et al 24 found an average hospital stay of 10, 13 and 10 days, respectively, in series of patients undergoing pancreatectomy. Postoperative fluid restriction, early oral intake and mobilization, effective analgesia and early removal of drains and catheters form, in general, the main recommendations suggested by these and other authors 8,[23][24][25] . While we agree with most of these measures, we do not practice fluid restriction, neither the early removal of abdominal drains.…”
Section: Results Results Results Resultsmentioning
confidence: 97%
“…The results of this undertaking are the Enhanced Recovery After Surgery (ERAS) protocols we know today (Table 1). [2][3][4][5][6][7][8][9][10][11][12][13][14] All ERAS protocols typically share the following features:…”
Section: Résumémentioning
confidence: 99%